(untitled) (Research, Society and Development, 2022)
Objective: The article’s purpose, through case study methodology, demonstrate one of the skeletal class III treatment techniques during mixed dentition and present the advantages of an early treatment. In the present case, a 9-year-old female patient, after clinical and radiographic examinations, confirmed skeletal class III malocclusion and immediately started treatment with the Haas expander associated with Petit Face Mask. The characteristics of the Class III pattern may become less intense with treatment and then resulting in a significant improvement in the patient’s function, aesthetic and psychological improvement.